(3MGTjI MLGRi Ydi TQM GdOQOjQ dQSGdJg JMaI GdENhGf aj af GdeYGfi hGdHjGfs - (3GdYOhj , MLGRj Hf YHO GdeWdH GdeGdcj,J (B1232 (3g` s
(3ChdgG (B:s
(3CeG HYO ajbhd HeWGdYI TQM s
(3BNQgG (B:s
(3bhdg hef Pdc bhdge EdN hGdMeO ddg s
(3GfXQ EjVGM Gdecfhf (B1/239s
(3JMaI GdENhGf GdCMeO GdOQOjQs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B244 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B67s
Keywords: (3GdHdGZIs